Quality of Financial Statements: Are Litigation Risk and Audit Quality the Determining Factors? - Fitri Nurlaela; R. Nelly Nur Apandi; Agus Widarsono (Nusantara Science and Technology Proceedings, 2020)
The purpose of this research is to examine the effect of litigation risk on the quality of financial statements as moderated by audit quality. The study focuses on financial statement quality by determining litigation risk. Using descriptive statistics and inferential method with a quantitative approach, this study using 55 manufacturing company's data which listed the Indonesia Stock Exchange. The results showed that litigation risk does not affect the quality of financial statements, audit quality has a significant effect on the quality of financial statements, and litigation risk to the quality of financial statements that are moderated by audit quality is declared not weakening. The results of this study contribute to stakeholders in analyzing the quality of corporate financial statements measuring by litigation risk.